2020
DOI: 10.2478/acph-2021-0020
|View full text |Cite
|
Sign up to set email alerts
|

Tryptanthrin exerts anti-breast cancer effects both in vitro and in vivo through modulating the inflammatory tumor microenvironment

Abstract: Tryptanthrin is an indole quinazoline alkaloid from the indigo-bearing plants, such as Isatis indigotica Fort. Typically, this natural compound shows a variety of pharmacological activities such as antitumor, antibacterial, anti-inflammatory and antioxidant effects. This study was conducted to assess the antitumor activity of tryptanthrin in breast cancer models both in vitro and in vivo, and to explore the important role of the inflammatory tumor microenvironment (TME) in the antitumor effects of tryptanthrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Because HCoV-NL63 is similar to SARS-CoV and COVID-19 in highly conserved sequence and structure, tryptanthrin may be developed as one of the coronavirus drugs [8]. Besides, tryptanthrin also has antibacterial [9], anti-tumor [10], anti-inflammatory [11] and antioxidant activity [12]. Indirubin is a treatment for chronic myeloid leukemia and also has antiviral [13], anti-inflammatory [14] and antioxidant [15] effects.…”
Section: Introductionmentioning
confidence: 99%
“…Because HCoV-NL63 is similar to SARS-CoV and COVID-19 in highly conserved sequence and structure, tryptanthrin may be developed as one of the coronavirus drugs [8]. Besides, tryptanthrin also has antibacterial [9], anti-tumor [10], anti-inflammatory [11] and antioxidant activity [12]. Indirubin is a treatment for chronic myeloid leukemia and also has antiviral [13], anti-inflammatory [14] and antioxidant [15] effects.…”
Section: Introductionmentioning
confidence: 99%
“…Another alkaloid structure, piperlongumine (Figure 6), appears to have anticancer properties via downregulating c-Met expression and NF-kB activity in renal, colon, lung, and prostate carcinoma cells (264)(265)(266)(267)(268). Harmine (269), fangchinoline (270), sinapine (271), gramine (272), cepharanthine (273), piperine (274,275), lamellarin D (276), ipobscurine (277), chelerythrine (278), dihydrochelerythrine (279), tryptanthrin (280), and neferine (Figure 6) (281) are some of the other alkaloid agents that exert significant anticancer activity through modulation of VEGF, AP-1, fibroblast growth factor receptor 4 (FGFR4)/ fibroblast growth factor receptor substrate 2a (FRS2a)-ERK1/ 2, NF-kB, Nrf-2/Kelch-like ECH-associated protein 1 (Keap-1), MMP-2, MMP-9, and STAT3.…”
Section: Alkaloidsmentioning
confidence: 99%
“…It inhibited cyclooxygenase 2 (COX-2) and 5-lipoxygenase (5-LOX) in cell-based assays and inhibited Trichophyton mentagrophytes , which causes tinea pedis (Tang et al, 2004 ). Zeng et al ( 2021 ) reported that tryptanthrin inhibited the proliferation, migration, and invasion of human breast adenocarcinoma Michigan Cancer Foundation-7 (MCF-7) cells, and regulated the level of related proteins in vitro. Tryptanthrin effectively inhibited tumor growth in 4 T1 murine breast cancer model; modulated expression levels of nitric oxide synthase 1 (NOS1), COX-2, and nuclear factor kappa-B (NF-κB) in mouse tumor tissues; and regulated some factors such as IL-2, IL-10, and TNF-α in mice (Zeng et al, 2021 ).…”
Section: Clinical Applications and Pharmacological Activities Of I Indigoticamentioning
confidence: 99%
“…Zeng et al ( 2021 ) reported that tryptanthrin inhibited the proliferation, migration, and invasion of human breast adenocarcinoma Michigan Cancer Foundation-7 (MCF-7) cells, and regulated the level of related proteins in vitro. Tryptanthrin effectively inhibited tumor growth in 4 T1 murine breast cancer model; modulated expression levels of nitric oxide synthase 1 (NOS1), COX-2, and nuclear factor kappa-B (NF-κB) in mouse tumor tissues; and regulated some factors such as IL-2, IL-10, and TNF-α in mice (Zeng et al, 2021 ). Indirubin possesses anti-tumor activity as shown by its ability to inhibit the growth of transplanted tumors and alleviate chronic myeloid leukemia (Xu et al, 2010 ).…”
Section: Clinical Applications and Pharmacological Activities Of I Indigoticamentioning
confidence: 99%